Anti-mGluR1 encephalitis: Case illustration and systematic review - Khojah, Osama; Makkawi, Seraj; Alghamdi, Saeed (Frontiers in Neurology, 2023)
Background The literature for immune-mediated neurological disorders is evolving like no other field of neurological illnesses. Many new antibodies or disorders have been described in the last decade. The cerebellum is a brain structure susceptible to these immune-mediated pathologies, and anti-metabotropic glutamate receptor 1 (mGluR1) antibody has a predilection to the cerebellar tissue. Anti-mGluR1 encephalitis is a rare autoimmune disease affecting the central and peripheral nervous systems, triggering an acute or subacute cerebellar syndrome with varying degrees of severity. Anti-mGluR1 encephalitis is a rare autoimmune disease affecting the central nervous system. We aimed to systematically review reported cases of anti-mGluR1 encephalitis and summarize their clinical presentation, management, outcomes, and case reports. Methods A search of the PubMed and Google Scholar databases was conducted and included all cases of anti-mGluR1 encephalitis published in English before October 1, 2022. A comprehensive systematic review was conducted using “metabotropic glutamate receptor type 1,” “mGluR1,” autoantibodies,” “autoantibodies,” “autoimmunity,” and “antibody” as keywords. The risk of bias assessment of the evidence was performed using appropriate tools. The qualitative variables were presented as frequency and percentage. Results Including our case, 36 cases of anti-mGluR1 encephalitis (19 males, median age 52.5 years, 11.1% pediatric cases) have been reported. The most common clinical manifestations are ataxia, dysarthria, and nystagmus. Initial imaging was normal in 44.4% of patients; however, 75% of patients showed abnormality later in the disease course. The first-line therapy options include glucocorticoids, intravenous immunoglobulin, and plasma exchange. Rituximab is the most commonly used second-line treatment. Complete remission was achieved in only 22.2% of patients, and 61.8% were disabled by the end of their course. Conclusion Anti-mGluR1 encephalitis manifests as symptoms of cerebellar pathology. Although the natural history has not been completely elucidated, early diagnosis with prompt initiation of immunotherapy could be imperative. Any patient suspected to have autoimmune cerebellitis should be tested for the presence of anti-mGluR1 antibody in the serum and cerebrospinal fluid. Escalation to an aggressive therapy approach should be applied in cases that do not respond to first-line therapies, and extended follow-up durations are required in all cases.